2009
DOI: 10.1097/aap.0b013e3181ac7d18
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective, Randomized Comparison Between Ultrasound-Guided Supraclavicular, Infraclavicular, and Axillary Brachial Plexus Blocks

Abstract: Adjunctive ultrasonography results in similar success rates, total anesthesia-related times, and block-related pain scores for the SCB, ICB, and AXB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
163
0
9

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 128 publications
(183 citation statements)
references
References 23 publications
(34 reference statements)
11
163
0
9
Order By: Relevance
“…Several recent studies have shown that the supraclavicular approach does not provide a shorter onset time or a more reliable block than infraclavicular or axillary blocks. [17][18][19] The ulnar nerve may be missed, with a failure rate as high as 36%. 17,18 The infraclavicular approach has been shown to be equivalent to, if not better than, the supraclavicular approach.…”
Section: Forearm and Handmentioning
confidence: 99%
See 3 more Smart Citations
“…Several recent studies have shown that the supraclavicular approach does not provide a shorter onset time or a more reliable block than infraclavicular or axillary blocks. [17][18][19] The ulnar nerve may be missed, with a failure rate as high as 36%. 17,18 The infraclavicular approach has been shown to be equivalent to, if not better than, the supraclavicular approach.…”
Section: Forearm and Handmentioning
confidence: 99%
“…The axillary approach is another interesting option with an onset time and quality of block similar to the infraclavicular block. 19 All approaches carry the risk of vascular puncture. Axillary blocks are preferred when the risk of bleeding secondary to vascular puncture is a concern, as they are superficial and performed in a compressible area.…”
Section: Forearm and Handmentioning
confidence: 99%
See 2 more Smart Citations
“…Some of these points can be illustrated by comparing three studies that weighed ultrasound-guided supraclavicular against infraclavicular block but arrived at very different results [12][13][14] (Table 1). Arcand et al 12 reported a higher incidence of anesthesia or analgesia in the five terminal nerve distributions of the brachial plexus with the supraclavicular block; Koscielnak-Nielsen et al 13 found the converse to be true; and Tran et al 14 found no difference.…”
Section: Variations In Techniquementioning
confidence: 99%